Pupil and salivary indicators of autonomic dysfunction in autism spectrum disorder. Issue 5 (29th May 2012) - Anderson, Christa J.; Colombo, John; Unruh, Kathryn E.
Abstract Dysregulated tonic pupil size has been reported in autism spectrum disorder (ASD). Among the possible sources of this dysregulation are disruptions in the feedback loop between norepinephrine (NE) and hypothalamic systems. In the current study, we examined afternoon levels of salivary alpha‐amylase (sAA, a putative correlate of NE) and cortisol (used to assess stress‐based responses) in two independent samples of children with ASD. We found a larger pupil size and lower sAA levels in ASD, compared to typical and clinical age‐matched controls. This was substantiated at the individual level, as sAA levels were strongly correlated with tonic pupil size. Relatively little diurnal variation in sAA taken in the home environment in the ASD group was also observed, while typical controls showed a significant linear increase throughout the day. Results are discussed in terms of potential early biomarkers and the elucidation of underlying neural dysfunction in ASD. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 465–482, 2013